An Analysis Of Firm-Specific, Industry Specific, And Macroeconomic Determinants Influencing Bank Profitability In Indonesia - Handriani, Eka; Anggara, Sebastian Billy (Faculty of Economics and Business | Universitas Diponegoro, 2025)
In this study, we examine the key determinants of bank profitability in Indonesia over the period 2013-2021. The research categorizes the factors influencing bank profitability into two broad groups: bank-specific (internal) factors and industry- and macroeconomic-specific (external) factors. The empirical findings of this study reveal that several internal and external factors significantly influence bank profitability in Indonesia. First, bank size demonstrates a significant positive effect on financial performance, as indicated by a t-value of 2.93. Larger banks tend to benefit from economies of scale, operational efficiency, and broader market access, enabling them to enhance profitability. Capital adequacy also shows a significant positive relationship with profitability t-value 2.72, reflecting that well-capitalized banks are better equipped to absorb risk, support asset growth, and maintain investor confidence. In contrast, credit risk does not exhibit a statistically significant impact on profitability t-value 1.39. This may be due to improved risk management practices, portfolio diversification, and regulatory support, which mitigate the effect of credit defaults on financial outcomes. The study also finds strong support for the role of management efficiency, with a significant t-value of 2.24. Efficient banks can reduce operational costs, allocate resources strategically, and respond effectively to market changes. However, market concentration does not appear to positively affect profitability t-value -1.63, possibly due to complacency, regulatory burdens, and reduced competition in highly concentrated markets. Regarding macroeconomic variables, inflation shows a negative but statistically weak relationship with bank profitability t-value -1.08, indicating potential erosion of income through increased costs and credit risk. Lastly, economic growth exerts a significant positive influence t-value 2.08, reinforcing the notion that expanding economic activity enhances loan demand, improves asset quality, and supports banking sector performance.